Soliton solutions of time-fractional modified Korteweg-de-Vries Zakharov-Kuznetsov equation and modulation instability analysis - Onder, Ismail; Secer, Aydin; Bayram, Mustafa (IOP Publishing Ltd, 2024)
In this paper, we explore analytical solutions for the (3+1)-dimensional time-fractional modified Korteweg-de Vries Zakharov-Kuznetsov equation, which incorporates a conformable derivative. Our interest in this model is driven by its significant role in simulating ion-acoustic waves in magnetized plasma. We adopt the unified Riccati equation expansion method and the new Kudrashov method to discover soliton solutions. Our approach uncovers various soliton types, such as kink, singular, periodic-singular, and bright solitons. We conduct a thorough analysis of how different parameters affect wave propagation, enhancing our study with descriptive figures and insightful observations. Furthermore, we delve into the modulation instability characteristic of this model. The influence of specific parameters, like wave number and the order of the conformable derivative, on wave dynamics is demonstrated through detailed visualizations. We also present 2D and 3D graphical representations of these solutions.
Keywords: modified Korteweg-de Vries Zakharov-Kuznetsov equation; soliton solution; unified Riccati equation expansion method; new Kudryashov method; KDV; Physics